2014
DOI: 10.3390/molecules191016240
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Important Molecules of Plant Interactions with the Environment

Abstract: Flavonoids are small molecular secondary metabolites synthesized by plants with various biological activities. Due to their physical and biochemical properties, they are capable of participating in plants' interactions with other organisms (microorganisms, animals and other plants) and their reactions to environmental stresses. The majority of their functions result from their strong antioxidative properties. Although an increasing number of studies focus on the application of flavonoids in medicine or the foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
667
1
28

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 963 publications
(714 citation statements)
references
References 181 publications
(180 reference statements)
18
667
1
28
Order By: Relevance
“…This wild species has effective resistance mechanisms to different abiotic stress factors, but also to some biotic agents, like aphids (Alvarez et al, 2006), nematodes (Austin et al, 1993) or fungi (Lokossou et al, 2010). In this context, higher TPC, TFC and AA were actually expected for the wild species, all three physiological traits taken into consideration being actively involved in the resistance mechanisms (Lattanzio et al, 2006;Mierziak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This wild species has effective resistance mechanisms to different abiotic stress factors, but also to some biotic agents, like aphids (Alvarez et al, 2006), nematodes (Austin et al, 1993) or fungi (Lokossou et al, 2010). In this context, higher TPC, TFC and AA were actually expected for the wild species, all three physiological traits taken into consideration being actively involved in the resistance mechanisms (Lattanzio et al, 2006;Mierziak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…maintaining the redox state of the cell are the phenolic compounds, due to their strong antioxidant capacity. Phenols may be found constitutively in plant cells, but it was demonstrated that their quantity is rapidly increasing, by de novo synthesis, in the presence of a stressful factor (JacoboVelázquez and Cisneros-Zevallos, 2012; Mierziak et al, 2014). In this way, phenolic compounds are directly involved in the plant defence mechanisms and in overcoming abiotic stress conditions (Ramakrishna and Ravishankar, 2011).…”
Section: Plant Materialsmentioning
confidence: 99%
“…57 Flavonoids are implicated in many important functions in plant including signaling to symbiotic bacteria and they may play an important role in plant resistance against pathogenic bacteria and fungi. 58 Flavonoids may enhance plant resistance to pathogens in several different ways: (1) by quenching the reactive oxygen species which form in plants after infection, (2) by inhibition of pathogen's digestive enzymes as a result of chelating metals required for their activity, (3) by induction of the hypersensitivity reaction and programmed cell death, (4) and by tightening of the plant cell structure by altering indole-3-acetic acid activity. 59 In addition, flavonoids, can stimulate or inhibit insect feeding and oviposition.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Also, the flavonoids are beneficial to plants themselves from participating in plants' interactions with other organisms and their reactions to environmental stresses. 2 S. chamaejasme synthesizes a group of flavonoids, which gained much attention due to their biological activities to cancer cells and virus.…”
mentioning
confidence: 99%